High mortality rates in men initiated on anti-retroviral treatment in KwaZulu-Natal, South Africa. - Kogieleum Naidoo; Razia Hassan-Moosa; Nonhlanhla Yende-Zuma; Dhineshree Govender; Nesri Padayatchi; Halima Dawood; Rochelle Nicola Adams; Aveshen Govender; Tilagavathy Chinappa; Salim Abdool-Karim; Quarraisha Abdool-Karim (PLoS ONE, 2017)
In attaining UNAIDS targets of 90-90-90 to achieve epidemic control, understanding who the current utilizers of HIV treatment services are will inform efforts aimed at reaching those not being reached. A retrospective chart review of CAPRISA AIDS Treatment Program (CAT) patients between 2004 and 2013 was undertaken. Of the 4043 HIV-infected patients initiated on ART, 2586 (64.0%) were women. At ART initiation, men, compared to women, had significantly lower median CD4+ cell counts (113 vs 131 cells/mm3, p <0.001), lower median body mass index (BMI) (21.0 vs 24.2 kg/m2, p<0.001), higher mean log viral load (5.0 vs 4.9 copies/ml, p<0.001) and were significantly older (median age: 35 vs. 32 years, p<0.001). Men had higher mortality rates compared to women, 6.7 per 100 person-years (p-y), (95% CI: 5.8-7.8) vs. 4.4 per 100 p-y, (95% CI: 3.8-5.0); mortality rate ratio: 1.54, (95% CI: 1.27-1.87), p <0.001. Age-standardised mortality rate was 7.9 per 100 p-y (95% CI: 4.1-11.7) for men and 5.7 per 100 p-y (95% CI: 2.7 to 8.6) for women (standardised mortality ratio: 1.38 (1.15 to 1.70)). Mean CD4+ cell count increases post-ART initiation were lower in men at all follow-up time points. Men presented later in the course of their HIV disease for ART initiation with more advanced disease and experienced a higher mortality rate compared to women.